Nigerian Shipping Industry and Trade: Array - Ebiere, Stephanie Odubo (Danubius Working Papers, 2020)
Shipping truly has been an important catalyst in boosting the Nigerian economy because when mineral oil was first discovered in Nigeria, it had to be exported to other countries of the world and ships where used to make this transportation across the sea to other countries and continents bordered by the sea. However, this does not displace other means of transportation as they are also very important and needed to get goods to and from the ship and for other purposes as well. In this article I will explain the history of shipping in Nigeria and how that has affected the present shipping industries and furthermore to make a connection between the shipping industry and trade in Nigeria